EFFICIENCY ANALYSIS OF JAVA'S REGIONAL BANKS IN LENDING ALLOCATION - Pratama, Agung Yuda; Setyo Tri Wahyudi (Contemporary Studies in Economic, Finance and Banking, 2024)
This research examines the efficiency of lending distribution by Regional Development Banks (RDBs) in Java, Indonesia, using Data Envelopment Analysis (DEA) and panel regression analysis. It analyzes financial data from 2015-2022 to identify factors affecting lending distribution efficiency. Key variables include Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Operating Expenses to Operating Income (OER), and regional government funds percentage (LGFR). the study identifies that among the variables examined, only LDR significantly impacts the lending efficiency of RDBs. This finding underscores the critical role of effective deposit to loan conversion in enhancing RDB operational performance, while other factors such as CAR, NPL, OER, and LGFR do not show a statistically significant effect. This research contributes to the banking efficiency literature by highlighting the importance of optimizing LDR to improve the operational efficiency of RDBs. It offers new insights into the operations of regional banks and their role in regional economic growth, especially in Java.